Anxiety-like behaviour assessments of adolescent rats after repeated maternal separation during early life. Issue 8 (23rd May 2018) - Jin, Shengtao; Zhao, Yanan; Jiang, Yinghong; Wang, Yanyu; Li, Changjiang; Zhang, Deli; Lian, Bo; Du, Zhongde; Sun, Hongwei; Sun, Lin
Abstract : Maternal separation (MS) plays a central role in developing physiology and psychology during the individual ontogeny process. MS is used to research the neurobiological mechanisms of mental disorders and early life stress. In this study, we investigated the effects of repeated MS and early handling (EH) on locomotor activity in an open-field test, a light–dark box test and an elevated plus-maze test of adolescent rats. The results showed that MS reduced locomotor activities in the open-field test, and increased anxiety-like behaviours in the light–dark box test and the elevated plus-maze test in adolescent rats. These tests indicated that early life stress caused by MS might induce anxiety-like behaviours during adolescence. However, compared with the control group, both the MS and EH groups showed conflicting anxiety levels. The results also suggested that females were more prone to showing anxiety-like behaviour compared with males when suffering from high-intensity stimulation. However, because of the low anxiety level associated with EH, the sex difference in behaviour was not significant. The present study provides novel insights into the effects of MS and EH on behaviour, which shows unique anxiety levels different in adolescent male and female rats.